2007
DOI: 10.2307/4541092
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Diversification and Species Richness in Amphibians

Abstract: Geographic patterns of species richness ultimately arise through the processes of speciation, extinction, and dispersal, but relatively few studies consider evolutionary and biogeographic processes in explaining these diversity patterns. One explanation for high tropical species richness is that many species-rich clades originated in tropical regions and spread to temperate regions infrequently and more recently, leaving little time for species richness to accumulate there (assuming similar rates of diversific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
212
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(245 citation statements)
references
References 0 publications
29
212
4
Order By: Relevance
“…Synteny between Hyla and Xenopus Chromosomes are largely conserved between H. arborea and X. tropicalis, despite divergence time estimates ranging from 165 to 305 million years (Aris-Brosou and Yang, 2002;Wiens, 2007). A previous study demonstrated conserved synteny across H. arborea, Rana temporaria, Bufo siculus and X. tropicalis at chromosome 1 (Brelsford et al, 2013), with one small segment of the X. tropicalis chromosome found on a different chromosome in H. arborea.…”
Section: Discussionmentioning
confidence: 99%
“…Synteny between Hyla and Xenopus Chromosomes are largely conserved between H. arborea and X. tropicalis, despite divergence time estimates ranging from 165 to 305 million years (Aris-Brosou and Yang, 2002;Wiens, 2007). A previous study demonstrated conserved synteny across H. arborea, Rana temporaria, Bufo siculus and X. tropicalis at chromosome 1 (Brelsford et al, 2013), with one small segment of the X. tropicalis chromosome found on a different chromosome in H. arborea.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the estimated dates of hyloid origin [130-152 Mya, confidence limits, 108-208 Mya (7,19,36,45,51) (24,35), hylids (36,45), hemiphractines (50)]. This uncertainty makes it difficult to date their origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent analyses have dated the divergence of Ceratophrys from Lepidobatrachus to the latest Oligocene or Miocene [12.7-26.1 (45, 50)], results that are clearly incompatible with the attribution of either Baurubatrachus or Beelzebufo to the crown group. Moreover, based on the relatively low levels of genetic divergence among extant hyloids (45), some analyses also date the main hyloid radiation (i.e., without myobatrachids or Calyptocephalella) as occurring at, or soon after, the Cretaceous-Paleogene boundary [65-55 Mya (confidence limits 52-84 Mya) (45,50,51)]. This finding is difficult to reconcile with the presence of ceratophryines (or even stem-ceratophryines) in Madagascar at 70-65 Mya, even allowing for confidence limits, as the island was isolated from at least 80 Mya (3).…”
Section: Discussionmentioning
confidence: 99%
“…The latter was enhanced by the fact that evolutionary studies of larval morphological characters made use of conflicting phylogenetic hypotheses, some of which were inferred from the very same larval characters (6)(7)(8)(9)(10). Recent molecular studies using different data sources and methods have converged on very similar phylogenetic hypotheses for Anura (11)(12)(13)(14)(15)(16)(17)(18). Together, they provide a consensus tree that allows us to explore patterns of morphological variation among extant tadpoles with unprecedented accuracy and detail.…”
mentioning
confidence: 99%